2013
DOI: 10.1186/1744-9081-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Reduced orbitofrontal cortical thickness in male adolescents with internet addiction

Abstract: BackgroundThe orbitofrontal cortex (OFC) has consistently been implicated in the pathology of both drug and behavioral addictions. However, no study to date has examined OFC thickness in internet addiction. In the current study, we investigated the existence of differences in cortical thickness of the OFC in adolescents with internet addiction. On the basis of recently proposed theoretical models of addiction, we predicted a reduction of thickness in the OFC of internet addicted individuals.FindingsParticipant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 29 publications
2
84
1
1
Order By: Relevance
“…In a large study of less severe problem gamblers, no group differences were observed in brain volumes [van Holst et al, 2012]. One small study in internet addiction showed lower cortical thickness in the OFC [Hong et al, 2013], with another reporting lower volume in dorsolateral prefrontal cortex (DLPFC) [Yuan et al, 2011] and two studies suggesting lower ACC volumes [Yuan et al, 2011; Zhou et al, 2011]. Two small studies in internet gaming disorders reported decreased volumes in OFC [Weng et al, 2013; Yuan et al, 2013], and two larger studies reported smaller volumes in cingulate cortex [Lin et al, 2014; Wang et al, 2015] with single studies reporting decreases in DLPFC [Wang et al, 2015], inferior frontal [Lin et al, 2014], superior parietal [Wang et al, 2015] and inferior parietal [Yuan et al, 2013] cortices.…”
Section: Introductionmentioning
confidence: 99%
“…In a large study of less severe problem gamblers, no group differences were observed in brain volumes [van Holst et al, 2012]. One small study in internet addiction showed lower cortical thickness in the OFC [Hong et al, 2013], with another reporting lower volume in dorsolateral prefrontal cortex (DLPFC) [Yuan et al, 2011] and two studies suggesting lower ACC volumes [Yuan et al, 2011; Zhou et al, 2011]. Two small studies in internet gaming disorders reported decreased volumes in OFC [Weng et al, 2013; Yuan et al, 2013], and two larger studies reported smaller volumes in cingulate cortex [Lin et al, 2014; Wang et al, 2015] with single studies reporting decreases in DLPFC [Wang et al, 2015], inferior frontal [Lin et al, 2014], superior parietal [Wang et al, 2015] and inferior parietal [Yuan et al, 2013] cortices.…”
Section: Introductionmentioning
confidence: 99%
“…90 IA has also been found to be associated with lower levels of gray matter and consequent changes in motor control, thinking, motivation, emotions, craving, and decisionmaking. 91 Furthermore, research suggests that male Internet addicts have morphometric brain abnormalities, including a significantly lower orbitofrontal cortical thickness in comparison with healthy controls, 92 decreased right frontal pole gray matter volume, better functional connectivity between their right frontal pole and the left ventral striatum, and a higher amplitude of low-frequency fluctuation in their bilateral ventral striatum, suggesting an impaired ability to focus on long-term goals if distracted. 93 Studies using electroencephalography indicate that individuals with IA allocate their attention differently than healthy controls, suggesting impaired information processing and response inhibition in IA, [94][95][96][97] leading to impulsive decisions, which may contribute to renewed engagement in the addictive behavior irrespective of potential negative consequences.…”
mentioning
confidence: 99%
“…Recently various morphometric studies on cortical centres of the brain with IA have found possible neural mechanisms. Brain regions which are involved in executive control, such as the orbitofrontal cortex, dorsolateral prefrontal cortex (dlPFC), and anterior cingulate cortex (Acc) showed decreased grey matter volume [23][24][25][26] and reduced cortical thickness [27,28]. In addition, cortical volume loss in striatum and insular cortex is also measured [29,30].…”
Section: Structural and Chemical Alterations In Brain With Iamentioning
confidence: 99%